The Lithuanian evangelical-reformat schools - Laurynaitis , V. (Psichologija, 1972)
The Lithuanian Evangelic-Reformatic schools have been investigated rather little. The organization of those schools, teachers, pupils, teaching and educational aims and methods are characterized in the article. As reformers and their schools struggled against reactionary catholic priests and the Order of the Jesuits, the presumption arises that the schools had progressive traits. Two main aims had been raised by Reformatic schools: to bring up a bright-minded secular personality by means of works by Roman authors and raise its morality by spreading religious feelings. In the first respect those schools were progressive but the spread of religious feelings was a serious obstacle in the development of personality and national culture of the country. Such ideological scantiness of the above mentioned schools is confirmed by teaching and educational methods of Kėdainiai higher school and its religious needs. In some respect the reformers are of great significance: in their schools they enlightened national youth and understood the importance of the Lithuanian language, they published books in Lithuanian though the subject-matter of these books was religious. Moreover, the children in schools, especially in primary ones, were taught in their mother tongue. Thus, the reformers had paid a certain contribution to the national culture.
Keywords: history of pedagogy; evangelic-reformatic schools